O direito natural em Santo Tomás de Aquino: uma análise histórica visando desfazer equívocos sobre o autor e sua obra - Tamiello, Vitor (2024)
Through historical and bibliographical research, this paper seeks to analyze the reasons why Saint Thomas Aquinas' natural law has become scarce in academic and legal environments. The thesis is that many people are unaware of and many others misinterpret Aquinas' legal doctrine, motivated basically by three reasons: prejudice against the author – a “catholic medievalist” – and his main work – a supposed “apologetic compendium”; confusion between classical natural law and modern natural law; and misunderstanding about the capacity of such doctrine to participate in contemporary legal debates. After extensive historical analysis, it is found that Aquinas' natural law is a profound synthesis of three pillars of western civilization: greek philosophy, roman law, and christian tradition. It is also a doctrine that is a signatory of classical realism, using the prudential experience of the jurist and all the elements available to him to make justice effective in the specific case, always using natural law as a guideline. It is concluded that this is a legal doctrine based, above all, on reason – not on religious dogmas –, free from the criticisms made against modern natural law and, furthermore, fully capable of illuminating academic debates and of being effectively applied in current practical cases. For these reasons, Thomas Aquinas should be read again, but from a new perspective, free of prejudice and open to the greatness of the classics